Traumatic brain injury and bipolar psychosis in the Genomic Psychiatry Cohort. Issue 4 (29th July 2015) - Cieslak, Kristina; Pato, Michelle; Buckley, Peter; Pato, Carlos; Sobell, Janet L.; Medeiros, Helena; Zhao, Yuan; Ahn, Hongshik; ,; Malaspina, Dolores
Abstract : Approximately three million individuals in the United States sustain traumatic brain injury (TBI) every year, with documented impact on a range of neurological and psychiatric disturbances including mania, depression, and psychosis. Identification of subsets of individuals that may demonstrate increased propensity for posttraumatic symptoms and who may share genetic vulnerabilities for gene‐environment interactions can enhance efforts to understand, predict, and prevent these phenomena. A sample of 11, 489 cases from the Genomic Psychiatry Cohort (GPC), a NIMH‐managed data repository for the investigation of schizophrenia and bipolar disorder, was used for this study. Cases were excluded if TBI was deemed causal to their mental illness. A k‐ means clustering algorithm was used to probe differences between schizophrenia and bipolar disorder associated with variables including onset age, hallucinations, delusions, head injury, and TBI. Cases were separated into an optimum number of seven clusters, with two clusters including all cases with brain injury. Bipolar disorder with psychosis and TBI were significantly correlated in one cluster in which 72% of cases were male and 99.2% sustained head injury. This cluster also carried the longest average period of unconsciousness. This study demonstrates an association of TBI with psychosis in a subset of bipolar cases, suggesting that traumatic stressors may have the ability to impact gene expression in a vulnerable population, and/or there is a heightened occurrence of TBI in individuals with underlying psychosis. Further studies should more closely examine the interplay between genetic variation in bipolar disorder and susceptibility to psychosis following TBI. © 2015 Wiley Periodicals, Inc.